Building Student Ownership and Responsibility: Examining Student Outcomes from a Research-Practice Partnership. Issue 3 (3rd July 2019) - Cannata, Marisa; Redding, Christopher; Nguyen, Tuan D.
Abstract: This article is situated at the intersection of two trends in education research: a growing emphasis on the importance of co-cognitive traits and the emergence of research-practice partnerships to more effectively scale effective practices. Our partnership focused on building student ownership and responsibility for their learning, which means creating school-wide practices that foster a culture of learning and engagement among students. We find no evidence of an overall relationship between the student ownership and responsibility innovation and student outcomes that is robust to model specification. However, when results are separated by school, two schools each saw increased student grades and fewer absences that persisted across both years of implementation. We also use qualitative data about the quality of implementation to understand how school-level engagement in the improvement partnership may be related to observed outcomes.